METEOROLOGICAL FACTORS AFFECTING DIURNAL VARIATIONS OF SOIL MOISTURE (CASE STUDY: PANCAWATI CARINGIN DISTRICT, BOGOR) - Andira Cahyarani P., Geraldin
Soil moisture is influenced by meteorological factors, such as rainfall, air temperature, relative humidity, and solar radiation, each of which has an influence on different soil depths. This research examines the characteristics of soil moisture at various depths and its controlling factors based on available data in the mountains of Bogor. This research method is based on correlation analysis and diurnal variation of controlling factors (rainfall, solar radiation, relative humidity, and air temperature) and their correlation at soil depths of 25 cm, 50 cm, 75 cm, and 100 cm. The analysis results show that soil moisture fluctuations are influenced by air temperature, solar radiation, rainfall and relative humidity. The controlling factor that most influences diurnal variations at depths of 25 cm, 50 cm, 75 cm and 100 cm, namely variables at the same two hours times in the top layer. Lag correlation analysis shows that controlling factors directly influence soil moisture at all depths.